La dette écologique : d'une notion politique à un concept philosophique ? - Delphine Pouchain (Développement Durable et Territoires)
The notion of ecological debt emerged in the 1990's. Originally, it is a matter of debt which developed countries owe to developing countries. It will quickly become an argument to cancel the financial debt of developing countries. Then the question of its evaluation will arise. Next its meaning will be widened, in particular in the sense of a debt that men owe to nature. Despite some questions which seems crippling, this notion remains a relevant philosophical concept, or at least a stimulating one.